The effect of surface treatment with bonding agents on the shear bond strength between acrylic artificial teeth and thermoplastic nylon denture bases: an experimental study - Lubis, Lely Khairani; Ritonga, Putri Welda Utami (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRAKIntroduction: Surface treatment with a bonding agent can improve the bond between acrylic artificial teeth and thermoplastic nylon denture bases. Thermoplastic nylon denture bases often experience weak bonding issues with acrylic artificial teeth, which can lead to fracture or debonding of the denture from the base. This study aims to analyze the effect of various bonding agents on the shear bond strength between acrylic artificial teeth and thermoplastic nylon denture bases. Methods: A laboratory experimental study with post-test-only control group design was conducted on 32 samples of acrylic artificial teeth (maxillary central incisors) with cylindrical thermoplastic nylon bases (18×20 mm). The samples were divided into four groups: control, OptiBond Universall®, Tetric N-Bond Universall®, and 3M ESPE Single Bond Universall®. Shear bond strength testing was performed using a Universal Testing Machine (crosshead speed: 0.5 mm/min). Data were analyzed by one-way ANOVA followed by LSD post hoc testing (α=0.05). Results: The mean shear bond strengths were 0.453 ± 0.292 MPa (control), 0.896 ± 0.189 MPa (OptiBond), 1.684 ± 0.382 MPa (Tetric N-Bond), and 2.648 ± 0.221 MPa (3M ESPE), with significant differences between groups (p=0.001). Conclusion: Surface treatment with bonding agents significantly increased shear bond strength, with 3M ESPE Single Bond Universal® providing the highest bond strength compared to OptiBond Universall® and Tetric N-Bond Universall®.KEY WORDS: bonding agent, shear bond strength, acrylic artificial teeth, thermoplastic nylon.Efek surface treatment bonding agent pada kekuatan ikatan geser gigi artifisial akrilik dengan basis gigi tiruan nilon termoplastik: Studi eksperimentalABSTRAKPendahuluan: Surface treatment dengan bonding agent dapat meningkatkan perlekatan gigi artifisial akrilik dengan basis gigi tiruan nilon termoplastik. Basis gigi tiruan nilon termoplastik sering mengalami masalah ikatan yang lemah terhadap gigi artifisial akrilik, yang dapat menyebabkan fraktur atau lepasnya gigi tiruan dari basis. Penelitian ini bertujuan menganalisis pengaruh berbagai bonding agent terhadap kekuatan ikatan geser antara gigi artifisial akrilik dengan basis gigi tiruan nilon termoplastik. Metode: Penelitian eksperimental laboratoris dengan desain post-test only control group pada 32 sampel gigi artifisial akrilik insisivus sentralis rahang atas dengan basis nilon termoplastik silinder (18×20 mm). Sampel dibagi empat kelompok: kontrol, OptiBond Universall®, Tetric N-Bond Universal®, dan 3M ESPE Single Bond Universal®. Uji kekuatan ikatan geser dilakukan dengan Universal Testing Machine (crosshead 0,5 mm/menit). Data dianalisis dengan One-Way ANOVA dan uji LSD (α=0,05). Hasil: Rerata kekuatan ikatan geser adalah 0,453 ± 0,292 MPa (kontrol), 0,896 ± 0,189 MPa (OptiBond), 1,684 ± 0,382 MPa (Tetric N-Bond), dan 2,648 ± 0,221 MPa (3M ESPE), dengan perbedaan bermakna antar kelompok (p=0,001). Simpulan: Surface treatment bonding agent secara signifikan meningkatkan kekuatan ikatan geser, dengan 3M ESPE Single Bond Universall® memberikan hasil tertinggi dibandingkan OptiBond Universall® dan Tetric N-Bond Universall®. KATA KUNCI: bonding agent, kekuatan ikatan geser, gigi artifisial akrilik, nilon termoplastik.